2014
DOI: 10.1111/imj.12508
|View full text |Cite
|
Sign up to set email alerts
|

Association of better iron status biomarkers and coronary artery disease risk

Abstract: The present study indicated that the combination of SI and TIBC may have the best effect on CAD risk. Further studies are warranted to verify this preliminary result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…The authors concluded that high sTfR and low or high ferritin are predictors of poor outcome in diabetic patients with CAD. Similarly, Zhou et al (2014) investigated the association of iron status parameters with coronary artery disease (CAD) risk (n=540, aged 59.6±9.6) and found that serum iron and TIBC have the strongest association with CAD risk ((AUC 0.92 (0.90-0.95); 85%CI)).…”
Section: Iron Status and Cardiovascular Healthmentioning
confidence: 99%
“…The authors concluded that high sTfR and low or high ferritin are predictors of poor outcome in diabetic patients with CAD. Similarly, Zhou et al (2014) investigated the association of iron status parameters with coronary artery disease (CAD) risk (n=540, aged 59.6±9.6) and found that serum iron and TIBC have the strongest association with CAD risk ((AUC 0.92 (0.90-0.95); 85%CI)).…”
Section: Iron Status and Cardiovascular Healthmentioning
confidence: 99%
“…We speculated that the increase level of ferritin was mainly due to the underlying inflammation. A batch of studies have shown a similar positive correlation between ferritin and the risk of CAD 1,20,22,23,29,30,[44][45][46] . Xu et al found that elevated serum ferritin was independently significantly associated with carotid atherosclerosis in women (Xu et al 2017).…”
Section: Discussionmentioning
confidence: 82%
“…Fourthly, accumulated iron in adipocytes leads to adipocyte IR by increasing lipolysis and by decreasing insulin-stimulated glucose transport [2]. Adipocyte IR accelerates atherosclerosis [49].…”
Section: Discussionmentioning
confidence: 99%